Knowledge, attitude, and expertise of nurses in intensive care unit regarding oral and dental care in hospitalized patients. - Abbas Haghighat; Iman Mohammadi; Bahareh Tahani; Farshad Teimoori (Wolters Kluwer Medknow Publications, 2021)
Background: The purpose of this study was conducted to evaluate the knowledge, attitude, and practice of intensive care unit (ICU) nurses about oral and dental care in hospitalized patients.Materials and Methods: In this descriptive-analytic study, the statistical population included 214 nurses working in the ICU of the affiliated hospitals of Isfahan University in 1394. The level of knowledge, attitude, and practice of ICU nurses was assessed using questionnaires whose justifiability and stability were verified at the beginning of the study with a pilot study. Data were entered into SPSS software and tested by t-test, Spearman, one-way variance, and least significant difference test. The significance level was < 0.05.Results: The data of this study showed that the score of knowledge and performance in male nurses was significantly different from female nurses. There was a significant relationship between nurse's education and their knowledge score (P < 0.001). Furthermore, the performance score of nurses working in different parts was different too (P < 0.001).Conclusion: The findings showed that the knowledge and performance of female nurses about oral care were higher than men, but the attitude of the two sexes is almost the same. Nurses with lower educational degree had less knowledge, but their attitude and performance did not differ. The performance score of nurses working in ICU was different, but they had similar knowledge and attitudes.